Holocene sedimentation history in the Southern Novaya Zemlya Trench. - Levitan, Mikhail A; Belyaev, Nikolay A; Burtman, M V; Duplessy, Jean-Claude; Khusid, Tatyana A (PANGAEA, 2003)
It is shown that sediments accumulated in the Southern Novaya Zemlya Trench at both deglaciation and marine stages. Permanent sea ice sheet existed during the deglaciation, and glacier meltwater was intensely delivered to the bottom layer. Along with the dominant sediment supply from the Southern Island of Novaya Zemlya, southern continental sources also played a noticeable role at that stage. Seasonal sea ice freezing led to the formation of cold brines at the marine stage. Like paleoproductivity, these processes were irregular. Dissolution of calcareous benthic foraminiferal tests considerably intensified after about 7 ka BP owing to a stronger Atlantic water advection into the Western Arctic and consequent increase in paleoproductivity, whereas the relative role of southern sedimentary provenances decreased. Sedimentation rates were constant (45 cm/ka) during the entire marine stage.
(Table 1) Radiocarbon ages of Bivalvia shells obtained from core ASV13_1157, Novaya Zemlya Trench
Keywords: Age, 14C AMS; Age, 14C calibrated; Age, 14C milieu/reservoir corrected (-400 yr); Age, dated; Age, dated material; Age, dated standard deviation; Akademik Sergey Vavilov; Archive of Ocean Data; ARCOD; ASV13; ASV13_1157-GC; Calendar age; DEPTH, sediment/rock; GC; Gravity corer; off Novaja Zemlya; Sample ID